Relationship between Job Burnout and Quality of Life of Operation Room Technologists in Educational Hospitals Affiliated to Iran University of Medical Sciences in 2016-17 - Hanani, Sedigheh; Mohammadi, Sara; Amiri, Fardin; Azadi, Namamali (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Quality of life is affected by Job burnout, which can be caused by long-term exposure to occupational stress. The aim of this study was to determine the relationship between job burnout and quality of life of operation room technologists. Methods: In this cross-sectional descriptive-analytical study, 125 operation room technologists were randomly selected. The data were collected using three questionnaires: Demographic, Maslach Burnout Inventory (MBI), and WHO Quality of Life-BREF with 26 items, and analyzed using Spearman correlation test in SPSS software, and the significance level was considered as P≤0.05. Results: The mean of Job burnout score in terms of intensity, frequency, and quality of life was 47.88±17.50, 47.95±17.42, and 63.1±18.57, respectively. There was an inverse correlation between quality of life and job burnout in terms of Intensity (P<0.01) and frequency (P<0.05). Conclusions: Considering the significant inverse correlation between job burnout and quality of life, reducing the job burnout of employees can increase their quality of life and consequently prevent from the reduction of their productivity.